Ready for phase 5 - current status of ethnobiology in Southeast Asia - Hidayati, Syafitri; Francis, Merlin Franco; Bussmann, R. (BioMed Central, 2015)
Background: Southeast Asia is known for its rich linguistic, cultural and biological diversity. While ethnobiology in the west has benefitted greatly from intellectual and methodological advances over the last decades, the status of Southeast Asian ethnobiology is largely unknown. This study aims to provide an analysis of the current status of ethnobiology in Southeast Asia and outlines possibilities for future advancements. Methods: We accessed papers cited in the Scopus and Web of Science databases for the period of 1960 to 2014 using the current as well as previous names of the 11 Southeast Asian countries and various disciplines of ethnobiology as key words. We juxtaposed the number of publications from each country against its number of indigenous groups and languages, to see if ethnobiology research has addressed this full spectrum of ethnical diversity. The available data for the last ten years was analysed according to the five phases concept to understand the nature of studies dominating Southeast Asian ethnobiology. Results and conclusions: A total number of 312 publications were recorded in the databases for the period 1960-2014. Indonesia ranks highest (93 studies), followed by Thailand (68), Malaysia (58) Philippines (42), Vietnam (31), Laos (29), and other Southeast Asian countries (44). A strong correlation was found between the number of publications for each country, the number of indigenous groups, and the number of endangered languages. Comparing the data available for the period 2005-2009 with 2010-2014, we found a strong increase in the number of phase 5 publications. However, papers with bioprospecting focus were also on the rise, especially in Malaysia. Our study indicates that ethnobiologists still need to realise the full potential of the Biocultural Diversity of Southeast Asia, and that there is a strong need to focus more on socially relevant research. © Hidayati et al.; licensee BioMed Central.